Protection Shopping among Empires: Suspended Sovereignty in the Cocos-Keeling Islands. Issue 1 (31st December 2021) - Benton, Lauren; Clulow, Adam
Abstract: The political status of the Cocos-Keeling Islands, a group of twenty-seven small atoll islands in the Indian Ocean about 1, 700 miles west of Australia, remained unresolved from the time of the islands' settlement in 1827 until their effective incorporation into Australia in 1984. For a century and a half, protection shopping helped to create and sustain the islands' condition of suspended sovereignty. During the nineteenth century, the ruling family actively cultivated the protection of Dutch and British imperial agents and played one empire against the other. Imperial agents veered between intervention and restraint, and Cocos-Keeling islanders invoked protection to blunt rulers' power over them. The politics of protection continued into the twentieth century. Despite international attention to self-determination, the Cocos-Keeling Islands were not positioned for statehood, and full and effective integration into the British empire or Australia was perennially delayed. The territory's history as a place of seemingly permanent semi-autonomy illuminates a global pattern in which protection politics worked to suspend sovereignty and in some cases perpetuate social and racial inequalities, both inside political communities and across the international order.